Implementasi Pembelajaran Matematika Berbantuan Panggung Getar pada Siswa Tuna Rungu di SLB-B Pangudi Luhur Jakarta Barat - Fatwa, Alyan; Muslim, Suyitno; Khaerudin (Circle: Jurnal Pendidikan Matematika, 2025)
This study aims to describe the implementation of the Vibration Stage as a learning medium in mathematics instruction for deaf students at SLB-B Pangudi Luhur, West Jakarta. Auditory barriers in deaf students require adaptive strategies through multisensory approaches. The Vibration Stage utilizes sound vibrations, rhythm, light, and kinesthetic stimulation to support students’ understanding of mathematical concepts. This research employed a descriptive qualitative approach with deaf students as the subjects. Data were collected through observation, interviews, and documentation. The findings indicate that the use of the Vibration Stage enhanced students’ attention, comprehension of number concepts, as well as their social and emotional interactions during mathematics learning. This medium also assisted teachers in delivering materials more effectively and interactively, making the learning process more engaging and meaningful. Both students and teachers responded positively, as reflected in active participation, satisfaction, and increased learning motivation. In conclusion, the Vibration Stage proved to be an effective and innovative medium for improving engagement, learning outcomes, and classroom interaction in mathematics education for deaf students at SLB-B. Therefore, it can be considered a feasible alternative to enhance the quality of mathematics learning in special education contexts.